2009
DOI: 10.1007/s00127-009-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Housing services for people with mental disorders in England: patient characteristics, care provision and costs

Abstract: Quality standards may have to be defined and applied to ensure that all patients in housing services receive appropriate care. More input of mental health services may be required for the rehabilitation and recovery of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 13 publications
3
93
1
1
Order By: Relevance
“…In keeping with Priebe et al's [8] survey, we found that most service users were male, single, and unemployed and most had had previous mental health admissions. However, although most users of residential care and supported housing services had a primary diagnosis of psychosis, those in floating outreach services had less severe mental health problems (Priebe et al [8] reported that most service users had psychosis).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In keeping with Priebe et al's [8] survey, we found that most service users were male, single, and unemployed and most had had previous mental health admissions. However, although most users of residential care and supported housing services had a primary diagnosis of psychosis, those in floating outreach services had less severe mental health problems (Priebe et al [8] reported that most service users had psychosis).…”
Section: Discussionsupporting
confidence: 89%
“…Those in residential care had the highest number of needs but across all three types of supported accommodation most service user needs were being met. We also found lower rates of substance misuse (less than 20%) than in Priebe et al's survey [8], possibly because we used standardised assessment tools.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In presenting a recent national survey of housing services for people with mental disorders, Priebe et al (2009) provided a useful summary of the different supported accommodation that may be found in a locality.…”
Section: Forms Of Supported Accommodationmentioning
confidence: 99%